2002
DOI: 10.1074/jbc.m200156200
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Induces SHP-2 Association with Stat5, Nuclear Translocation, and Binding to the β-Casein Gene Promoter in Mammary Cells

Abstract: The Src homology 2 (SH2) domain containing proteintyrosine phosphatase SHP-2 contributes to prolactin receptor (PRLR) signal transduction to ␤-casein gene promoter activation. We report for the first time that SHP-2 physically associates with the signal transducer and activator of transcription-5a (Stat5a), an important mediator of PRLR signaling to milk protein gene activation, in the mouse mammary HC11 and the human breast cancer T47D cells when stimulated with prolactin (PRL) and human growth hormone, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 37 publications
3
51
0
Order By: Relevance
“…Consistent with previous reports (Yu et al, 2000;Chughtai et al, 2002;Chen et al, 2003), anti-STAT5 immunoprecipitation followed by anti-SHP-2 immunoblotting showed that SHP-2 constitutively associated with STAT5 independent of IL-3 stimulation in SHP-2 overexpressing cells (data not shown). Further in vitro GST pull down assay demonstrated that only the phosphatase fragment could pull down STAT5 (data not shown), suggesting that the SHP-2/STAT5 interaction is direct and that this association is mediated by the C-terminal part of SHP-2 but not the SH2 domains.…”
Section: Shp-2 Phosphatase Associates With and Dephosphorylates Stat5supporting
confidence: 80%
See 1 more Smart Citation
“…Consistent with previous reports (Yu et al, 2000;Chughtai et al, 2002;Chen et al, 2003), anti-STAT5 immunoprecipitation followed by anti-SHP-2 immunoblotting showed that SHP-2 constitutively associated with STAT5 independent of IL-3 stimulation in SHP-2 overexpressing cells (data not shown). Further in vitro GST pull down assay demonstrated that only the phosphatase fragment could pull down STAT5 (data not shown), suggesting that the SHP-2/STAT5 interaction is direct and that this association is mediated by the C-terminal part of SHP-2 but not the SH2 domains.…”
Section: Shp-2 Phosphatase Associates With and Dephosphorylates Stat5supporting
confidence: 80%
“…STAT5 is phosphorylated and activated by Jak family kinases, particularly Jak2; however, it is not fully understood how this transcription factor is inactivated. Previous reports have suggested that STAT5 might be dephosphorylated by tyrosine phosphatases PTP1B and SHP-2 in the prolactin, IL-2, and erythropoietin signaling pathways (Aoki and Matsuda, 2000;Yu et al, 2000;Chughtai et al, 2002;Chen et al, 2003), but the biological significance of their functional interactions remains uncharacterized.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we used the T47D human breast cancer cell line, which is a model system for studies of PRL and EGF action in breast cancer biology (Das and Vonderhaar, 1996a, b;Haraguchi et al, 1997;Gibson et al, 1999;Maus et al, 1999;Badache and Hynes, 2001;Lichtner et al, 2001;Chen et al, 2002;Chughtai et al, 2002;Kassenbrock et al, 2002;Acosta et al, 2003). We first tested responsiveness to each stimulus in these cells.…”
Section: Prl Promotes Erk-dependent Threonine Phosphorylation Of Egfrmentioning
confidence: 99%
“…The function of nuclear SHP-2 in prostate cancer could be involved in migration and invasion since nuclear expression correlated with extracapsular extension of the cancer. Prior studies have also reported SHP-2 in the nucleus [16][17][18][19]. Since SHP-2 lacks a typical nuclear localization signal sequence, it could be transported to the nucleus in association with proteins such as Gab1 [19].…”
Section: Correlation Of Shp-2 With Clinicopathological Parameters Andmentioning
confidence: 95%
“…Although it remains unclear, differential compartmentalization may alter SHP-2 function. For example, SHP-2 has been associated with the regulation of STAT5a as well as telomerase reverse transcriptase in the nucleus [17,19]. However, further studies are required to determine whether this PTP functions similarly in prostate cancer.…”
Section: Correlation Of Shp-2 With Clinicopathological Parameters Andmentioning
confidence: 99%